Hands-on financial modeling with Microsoft Excel 2019 : build practical models for forecasting, valuation, trading, and growth analysis using Excel 2019 /: build practical models for forecasting, valuation, trading, and growth analysis using Excel 2019. (2019) - Oluwa, Shmuel
No abstract available